PENGARUH EFIKASI DIRI DAN MATA KULIAH MICRO TEACHING TERHADAP KESIAPAN MENGIKUTI PROGRAM PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) PADA MAHASISWA PIPS FKIP UNIVERSITAS RIAU - Alfanisya Dasma Tri Ananda; Gimin; Filma Alia Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the influence of self-efficacy and the Micro Teaching course on the readiness of students in the Social Sciences Education Study Program (PIPS), Faculty of Teacher Training and Education (FKIP), University of Riau, to participate in the School Field Introduction Program (PLP). PLP is a basic stage in the formation of professional teachers, where students apply theoretical knowledge through observation, internships, and guided teaching practice in the school environment. Student readiness to undergo PLP is crucial, involving not only academic understanding but also the ability to adapt and interact in the work environment. In this context, self-confidence or self-efficacy, as well as practical experience gained from the Micro Teaching course, are identified as important elements that influence this readiness. The results showed that most students had a high level of PLP readiness, with the ability to interact and communicate with students being the most prominent aspect. Multiple linear regression analysis revealed that self-efficacy and the Micro Teaching course, both separately and together, had a positive and significant influence on student readiness to participate in PLP. In conclusion, this study found that most of the variation in PLP readiness can be explained by self-efficacy and the Micro Teaching course. These findings strongly emphasize the importance of self-confidence and practical experience gained from microteaching in preparing prospective teachers for the realities of the field. Therefore, it is recommended that students continue to develop their understanding and skills related to self-efficacy and microteaching to enhance their PLP readiness.